2021
DOI: 10.1136/postgradmedj-2021-140719
|View full text |Cite
|
Sign up to set email alerts
|

What gets resident physicians stressed and how would they prefer to be supported? A best–worst scaling study

Abstract: IntroductionPhysician burnout has severe consequences on clinician well-being. Residents face numerous work-stressors that can contribute to burnout; however, given specialty variation in work-stress, it is difficult to identify systemic stressors and implement effective burnout interventions on an institutional level. Assessing resident preferences by specialty for common wellness interventions could also contribute to improved efficacy.MethodsThis cross-sectional study used best–worst scaling (BWS), a type o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…However, there were other stressors that are common across all specialties. 6 Stressors that impacted residents included the novel pandemic, ethical dilemmas, depersonalization, role as a learner, training environment, and health concerns 3 ( Table 1 ). Of these, the novel pandemic and health concerns stressors are generalizable to the larger population, though the resident position brings unique components to each stressor that are role and position specific.…”
Section: Stressorsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, there were other stressors that are common across all specialties. 6 Stressors that impacted residents included the novel pandemic, ethical dilemmas, depersonalization, role as a learner, training environment, and health concerns 3 ( Table 1 ). Of these, the novel pandemic and health concerns stressors are generalizable to the larger population, though the resident position brings unique components to each stressor that are role and position specific.…”
Section: Stressorsmentioning
confidence: 99%
“… 1,5 These feelings are present across all specialties. 6 Vijay et al conducted a study of residents near the beginning of the pandemic and found that greater than 50% of residents had symptoms of emotional exhaustion, and only 42.9% felt valued by their institution. 1 Outside of work, Natsuhara et al described that the need to wear a mask leads to depersonalization because it hides emotions and the identities of practitioners, changing human interaction.…”
Section: Stressorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Various investigations carried out on burnout in resident physicians have shown that this group of professionals is especially vulnerable [3][4][5]. Burnout is described as having three dimensions (emotional exhaustion, depersonalization, and reduced personal accomplishment) [6].…”
Section: Introductionmentioning
confidence: 99%